Towards automated manufacturing of composites via thermally assisted frontal polymerization - Jordan, Walter Patrick, author; Yourdkhani, Mostafa, advisor; Zhao, Jianguo, committee member; Simske, Steve, committee member (Colorado State University. Libraries, 2024)
Current methods for the manufacturing and repair of fiber-reinforced thermoset composites are energy-intensive, slow, and costly due to extensive processing steps and expensive equipment required to achieve complete cure. This is especially true for large, complex geometries that require autoclaves and prolonged cure times. As a result, there is a need to develop faster, cost-effective, energy-efficient processes. With the implementation of rapid curing thermoset resins, the cure cycle can be reduced from hours to minutes. This research focuses on the development, implementation, and testing of these resin systems in the established fields of mobile additive manufacturing and filament winding to demonstrate unprecedented, rapid manufacturing of composite parts. Additive manufacturing of fiber-reinforced thermoset composites is desirable due to its inherent ability to produce custom, complex parts quickly, with minimal required tooling. By printing and simultaneously curing the composite as it is deposited, freeform unsupported structures with high mechanical properties can be created. One limitation of current additive manufacturing methods is the print volume associated with traditional gantry style additive manufacturing systems. By combining the highly desirable properties of additive manufacturing using rapid, thermally curable resin systems with the mobility of a mobile additive manufacturing system, large, mechanically sound structures with virtually no limitations on print volume can be created. Moreover, rapid curing thermoset resin systems have the potential to revolutionize traditional composite manufacturing processes. Due to its wide range of applications and its ubiquitous nature, filament winding serves as a natural starting point to do so. Traditional filament winding is typically a two-step manufacturing process, where the composite part is first wound on a rotating mandrel and then cured using autoclaves or ovens. By combining these processes on the winding machine, the labor involved in manufacturing, the energy required for curing, and the overall production time are significantly reduced. In this research, a mobile additive manufacturing robot is designed, validated, and optimized for accurate locomotion and fast, dimensionally accurate printing of composite structures with high fiber alignment and degree of cure. The capabilities of this system are exhibited throughout several demonstrations that involve printing unsupported structures upside-down, the manufacturing of a bridge strong enough for the robot to pass over, and bridging the material across a 60 cm gap. Additionally, a pre-existing filament winding machine is optimized for the manufacturing of large, geometrically unconstrained composite structures. Improvements in fiber volume fraction are achieved through processing changes and a thermal profile for dry fibers is established to facilitate identification of frontal polymerization.